A study on quality of work life in Pharmaceuticals Company in Nepal - Bhujel, Suraj (Journal of Balkumari College, 2019)
This research work was undertaken on behalf of Pharmaceutical company located in Nepal. It has been observed that the working efficiency bas been degraded to high extent as working staffs are unable to maintain their balance between personal as well as professional life. The purpose of this study is to identify the reason of low quality of work life of working staff in Nepal. This survey was conducted on 50 employees of the particular Company. For the sake of confidentiality the name of the company is not being disclosed.